Comunicação e constituição identitária: inter-relações com os sentidos atribuídos às práticas de consumo de aplicativos para smartphones - Scherrer, Rodrigo (2019)
The present thesis has as its theme the identity constitution and its interrelationship with practices of consumption in the use of mobile media communication. Based on a communicational perspective, we investigate how the identities are constructed in contemporaneity according to the meanings attributed to consumption practices of smartphone applications. In this sense, we adopt a diachronic approach in a context of identity crisis, in which individuals/subjects are taken as fragmented and, in this condition, resort to narratives to stabilize their identities, even if in a provisional way. The research aims to understand the relationship between these narratives and the consumption of applications, taken as a social practice. For this, it is necessary address a discussion on the ties built with the various communication technologies that someone has access through the meanings assigned to them, as a way to understand the differences marked by the use of smartphones and their applications in their life paths. We will also seek to identify relevant applications in the contexts of life, understanding how meanings attributed are associated with lifestyles. Methodologically, the corpus is formed by narratives woven by individuals residing in São Paulo, collected through in-depth interviews of the episodic type, which were analyzed semantically according to theory gathered about the topic. The results show that the applications are taken as part of the lives of individuals, being directly interwoven in their daily practices, constituting part of their identities. In order to deal with the communicational aspects, we used Baccega (1998, 2007, 2009), Jensen (2013) and Martín-Barbero (2003); on identities, Hall (2000, 2011), Dubar (2005, 2009) and Woodward (1999); consumption, Douglas and Isherwood (2006) and Slater (2002); on mobile communication, smartphones and applications, Silva (1999, 2006, 2007, 20013, 2017) Lupton (2015, 2016), among others.